Direct assessment of quality of care in an applied behavior analysis center. (11th July 2019) - Grauerholz‐Fisher, Emma; Vollmer, Timothy R.; Peters, Kerri P.; Perez, Brandon C.; Berard, Allison M.
Abstract: Momentary time sampling has been used to evaluate quality of care in several settings, including residential facilities and nursing homes. Given the growing number of behavior analysts providing center‐based applied behavior analysis (ABA) therapy to children with autism spectrum disorders, ABA centers are a new area in which assessing environmental indicators that might be correlated with the quality of care could be very important. Therefore, we extended these procedures to an ABA center, where we used momentary time sampling to assess staff behavior, client behavior, client condition, and environmental condition. The results demonstrated that this descriptive assessment can be a useful tool to obtain direct measures of variables that might affect quality of care. The general utility of this assessment, intervention plans for targets identified by this assessment, limitations of the assessment, and directions for future research in this area are discussed.